Undernutrition prevalence and its determinants among children below five years of age in Shabelle zone, Somali region, eastern Ethiopia - Abdi Guled, Rashid; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie; Balachew, Tefera; Assefa, Nega (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2017)
Introduction: Malnutrition is a major public health problem worldwide. More than half of under-five child deaths are due to undernutrition, mainly in developing countries. Ethiopia is among the highest in Sub-Saharan Africa. While, Somali region is the worst in Ethiopia. Objection: This study aims to assess the prevalence and determinants of undernutrition among under-five children living in Gode and Adadle districts of Shabelle Zone, Somali region.